Cyanobacteria from a Brazilian subtropical freshwater water body - Werner, Vera Regina; Martins, Mariellen Dornelles [UNESP]; Silva, Fernanda Oliveira da (Soc Botanica Sao Paulo, 2018)
Due to the undeniable importance of the role that cyanobacteria play in different ecosystems, and the new discoveries and periodic changes in their taxonomic classification, the main objective of this research was a taxonomic update of the cyanobacteria recorded in an artificial, subtropical freshwater water body. This work also aimed at the knowledge of the geographic distribution and frequency of the species throughout the study period. The analyzed pond (called Basin 7) is located in an environmental preservation area called Braskem Environmental Station (29 degrees 5157.3S and 51 degrees 2154.7W), which is part of the green belt that surrounds the set of companies of the Southern Petrochemical Complex of Rio Grande do Sul state (Brazil). The studied samples were taken from May 2000 to December 2015, using a plankton net (30 mu m), and floating thallus of cyanobacteria were collected directly by hand. Thirty-three species were identified and distributed in the orders Oscillatoriales (14), Synechococcales (12), Chroococcales (6) and Spirulinales (1). Phormidium Kutzing ex Gomont presented the highest species richness, with five species identified, and P. tergestinum (Kutzing) Anagnostidis & Komarek was the one with the highest frequency of occurrence (81.3%). Among the identified species, seven are especially important for being potentially toxic. Eucapsis pseudalpina Komarek & Hindak also stood out for its first recorded occurrence in Brazil, and Ancylothrix rivularis Martins & Branco, Arthrospira jenneri Stizenberger ex Gomont and Pannus cf. brasiliensis Malone et al. for their first recorded occurrence in Rio Grande do Sul state. For each species, diagnoses, basionyms and synonyms when appropriate, illustrations and comments are presented.
Keywords: Artificial pond; Biodiversity; Cyanoprokaryota; Petrochemical complex; Southernmost Brazil; Taxonomy